ESTIMATION OF ZAKAT PROCEEDS IN BANGLADESH: A TWO-APPROACH ATTEMPT - Rashed Jahangir; Mehmet Bulut (Bank Indonesia, 2022)
The purpose of this study is to calculate Zakat proceeds in Bangladesh by using both classical and contemporary or alternative Zakat calculation methods. The results reveal that the percentage of Zakat amount to GDP is significantly higher than the average, i.e., 2.5-3%; under the classical and alternative approaches, the Zakat proceeds are estimated as 3.79 and 2.33 percent of GDP, respectively.